SPEAK NO LAW WITHOUT JUSTICE: EVALUATING THE RETROSPECTIVE FORCE OF DECLARATIONS OF UNCONSTITUTIONALITY WITH SPECIFIC REFERENCE TO QWELANE V SAHRC & OTHERS (686/2018) [2019] ZASCA 167 (The Pretoria Student Law Review, 2021)
On 29 November 2019 the Supreme Court of Appeal handed down judgment in Qwelane v SAHRC & Others1 (Qwelane) wherein the notorious hate speech prohibition, section 10 of the Promotion of Equality and Prevention of Unfair Discrimination Act2 (PEPUDA), was declared unconstitutional and invalid. This decision, predicted by many and applauded by some,3 now awaits confirmation by the Constitutional Court. However, the focus of this article pertains not so much to the merits of the decision in Qwelane, but to the (possible) retrospective force of this judgment and more broadly to declarations of unconstitutionality and their retrospectivity in general. This article will evaluate whether or not it can be regarded as just and equitable to limit the retrospectivity of the Qwelane decision. This will be done by examining case law of a similar nature and by exploring the array of decisions taken under section 10 of PEPUDA. This inquiry will also consider the possibility of a special judicial arrangement to be made by the Constitutional Court, as well as some practical considerations that have to be regarded such as costs and the applicable procedural law. The arguments put forward are also applicable to future declarations of unconstitutionality. The task of the courts is rarely easy and their orders often inconvenient; more so where the injustice was caused by the very instrument that was formulated to protect our fundamental rights — the law. Yet, the severity of the task at hand should never move our judiciary to speak law without justice. For this purpose the current article will firstly examine the facts of Qwelane and thereafter we will discuss the theoretical underpinning of declarations of unconstitutionality and constitutional changes in this regard. This will be followed by an analysis of case law in which the retrospectivity of declarations of unconstitutionality was significant, whereafter the nature and scope of decisions taken under section 10 of PEPUDA will be evaluated. The injustice of (potentially) limiting the retrospectivity of Qwelane will then be considered and finally, the article will conclude by looking at certain procedural matters.
Keywords: Qwelane v SAHRC & Others; Supreme Court of Appeal; PEPUDA